Manajemen Asuhan Kebidanan Antenatal Care Pada Ny ”K” dengan Hiperemesis Gravidarum Tingkat I di Puskesmas Bara-Baraya Makassar : Management of Antenatal Care for Mrs. “K” with Hyperemesis Gravidarum Level I at Bara-Baraya Primary Health Center Makassar - Fahira, A. Nur Faiza; Saleha, Sitti; Diarfah, Andi Dian; Taherong, Ferawati (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction Hyperemesis gravidarum is a condition of an excessive nausea and vomiting. It is one of the complications of pregnancy that affects the health status of the mother and fetal growth and development. Nausea and vomiting are the most common disorders encountered in early pregnancy which are classified into three levels; namely level I (mild), level II (moderate), level III (severe). World Health Organization (WHO) on 2015, reported that cases of pregnant women experiencing hyperemesis gravidarum increased by 30.1%, the incidence occurred in Sweden 0.3%, California 0.55%, in Canada 0.8%, in China 10.8%, in Norway 0.9%, in Pakistan 2.2% and in Turkey 1.9% (Nurhidayanti, Sitti Saleha, Zelna Yuni Andriyani 2023). Method this study aims to carry out Antenatal Care Management for mothers with Hyperemesis Gravidarum Level I at the Bara-Barayya Primary Health Center Makassar. The case study conducted on Mrs. “K” was in accordance with the needs of the client and the authority of the midwife by carrying out 7-steps of Varney midwifery care management and documentation in the form of SOAP. Result The results of this study indicated that Mrs. “K” with Hyperemesis Gravidarum Level I expressed complaints of excessive nausea and vomiting and decreased appetite accompanied by dizziness and heartburn to interfere with her activities. Conclusion After making 6 home visits, Mrs. “K” was no longer experiencing nausea and vomiting, her appetite returned to normal, the general condition was good, the level of consciousness was composmentis, vital signs were within normal limits and on physical examination no abnormalities were found.